Effect of plasma immersion ion implantation on wear behavior of Ti-6Al-4V alloy - Assis Resende, Fabrícia; Silva, Maria Margareth; de Moares Oliveira, Rogerio; Silva, Carla; Pichon, Luc; Alves Radi, Polyana; Gonçalves dos Reis, Adriano [UNESP]; Aparecida Pereira Reis, Danieli (IOP Publishing, 2023)
Ti-6Al-4V alloy is ideal for use in the aeronautical and aerospace industries because of its excellent strength/weight ratio and corrosion resistance. However, its applications at high temperatures are vulnerable due to its high affinity for interstitial elements, such as nitrogen and oxygen. The plasma immersion ion implantation (PIII) technique, performed at high temperature, allows formation of modified layers that can improve the mechanical and tribological properties without compromising the corrosion resistance, which is a characteristic of this alloy. In this work, the samples were treated by PIII at three different temperatures (700, 800, and 900 °C) for 120 min of exposure to evaluate PIII on the mechanical behavior of Ti-6Al-4V alloy compared to data already available in the literature. The aim of this process is to improve surface mechanical properties of the Ti-6Al-4V alloy. The techniques used in this work were x-ray diffraction microhardness, glow discharge optical emission spectrometer, and wear testing in a ball-on-disk tribometer. The results indicate a significantly increased material resistance, with a reduced wear for all treated samples and a reduced friction coefficient for samples treated at 800 and 900 °C. The best results were for alloy treated at 800 and 900 °C, because they maintain the low coefficient throughout the test, which indicates better wear resistance.
Keywords: GDOES; PIII; Ti-6Al-4V; wear behavior